Clinical efficacy and safety of acupuncture versus Western medicine for insomnia: a systematic review and meta-analysis - Ma, Jun; Peng, Meng; Xu, Xue-Jiao (Frontiers in Neurology, 2025)
IntroductionInsomnia is a common sleep disorder that has a significant impact worldwide and seriously affects the quality of life of patients. Benzodiazepines and non-benzodiazepines are the conventional means of treating insomnia disorder in modern medicine. Acupuncture, as a traditional Chinese medicine therapy, is widely used in the treatment of insomnia disorder. A large number of clinical studies have confirmed the significant efficacy of acupuncture in the treatment of insomnia disorder. The aim of this study is to compare the efficacy and safety of acupuncture and sedative-hypnotic medications in the treatment of insomnia disorder through systematic review and Meta-analysis. To elucidate the efficacy and safety of acupuncture alone in the treatment of insomnia disorder.MethodsA comprehensive computerized literature search was conducted from January 2014 to December 2024 across multiple databases, including VIP Database, Wanfang Data, Cochrane Library, Embase, PubMed, and CNKI to identify studies on acupuncture therapy for patients with insomnia disorder. Two independent researchers performed the data extraction and literature screening processes following standardized protocols. The methodological quality of the included studies was assessed using the Cochrane risk-of-bias tool. Subsequently, a meta-analysis was performed using RevMan 5.4 software, incorporating data from 25 randomized controlled trials (RCTs) that met the predefined inclusion criteria.ResultsThe meta-analysis results, based on the Pittsburgh Sleep Quality Index (PSQI) scale scores, revealed that acupuncture regimens (MD: −2.52; 95% CI: −3.10 to −1.94; p < 0.00001; I2 = 94%; n = 2087) were significantly more effective compared to standalone medication.ConclusionAcupuncture has demonstrated significant efficacy in treating insomnia disorder, with preliminary evidence suggesting a potentially favorable safety profile and minimal adverse effects. However, existing studies exhibit inconsistencies in adverse event reporting and are generally limited by small sample sizes and methodological flaws. Therefore, future research should employ more rigorous study designs, expand participant cohorts, and conduct higher-quality investigations to further validate its efficacy and safety, thereby establishing more robust conclusions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, CRD420250653347.